The effect of lean methods and tools on the environmental performance of manufacturing organisations - Garza-Reyes, Jose Arturo; Kumar, Vikas; Chaikittisilp, Sariya; Tan, Kim Hua (Elsevier, 2018)
Evidence suggests that lean methods and tools have helped manufacturing organisations to achieve operational excellence, and in this way meet both traditional and contemporary organisational objectives such as profitability, efficiency, responsiveness, quality, and customer satisfaction. However, the effect of these methods and tools on environmental performance is still unclear, as limited empirical research has been conducted in this field. This paper therefore investigates the impact of five essential lean methods, i.e. JIT, autonomation, kaizen/continuous improvement, total productive maintenance (TPM) and value stream mapping (VSM), on four commonly utilised measures for the compliance of environmental performance, i.e. material use, energy consumption, non-product output, and pollutant releases. A correlation analysis modelled the relationship and effect of these lean methods on the environmental performance of 250 manufacturing organisations around the world. Structural equation modelling (SEM) was used as a second pronged verification approach to ensure the validity of the results. The results indicate that TMP and JIT have the strongest significance on environmental performance, whereas kaizen/continuous improvement only showed an effect on the use of materials and release of pollutants. Autonomation and VSM did not show any impact on environmental performance. The research holds important implications for industrialists, who can develop a richer knowledge on the relationship between lean and green. This will help them formulate more effective strategies for their simultaneous or sequential implementation. The paper extends our knowledge in the lean and green field by helping us to establish and explain the given relationships between five of the most important and commonly used lean methods and the environmental performance of manufacturing organisations. No previous research had considered the studied lean methods and environmental measures of performance.